The Dynamics of Capital Structure and Firm Value of Listed Industrial Goods in Nigeria - Muhammad, Maryam Isyaku; Abubakar, Mohammed; Kakanda, Mohammed Mahmud; Abubakar, Muhammad Abdul (Asian Journal of Empirical Research, 2020)
This paper aims to establish the effect of capital structure on the firm value of fourteen (14) quoted industrial goods companies operating in Nigeria for ten years (2008 to 2017). Data were obtained from the annual reports and accounts of the sampled firms. The indicators for capital structure comprises of long term and short term debt, while proxies for firm value include return on equity and share price. Multiple regressions were used to analyze the data. Long-term debt appeared negative and significant, with a return on equity. Like previous studies, value seems to be enhanced when industrial goods companies employ more internal funding, short term debt than long term debt. Regarding the share price, short-term debt significantly increases share price. However, long-term debt does not impact the share price of listed industrial goods companies in Nigeria. This paper recommends that management and board of directors should ensure the optimum level of financing mix in their composition of capital that enhances their business worth, particularly by minimising long-term loans.